Variations in Cardiovascular Structure, Function, and Geometry in Midlife Associated With a History of Hypertensive Pregnancy - Boardman, Henry; Lamata, Pablo; Lazdam, Merzaka; Verburg, Ashley; Siepmann, Timo; Upton, Ross; Bilderbeck, Amy; Dore, Rhys; Smedley, Clare; Kenworthy, Yvonne; Sverrisdottir, Yrsa; Aye, Christina Y.L.; et al. (Hypertension (Dallas, Tex. 1979), 2020)
Hypertensive pregnancy is associated with increased maternal cardiovascular risk in later life. A range of cardiovascular adaptations after pregnancy have been reported to partly explain this risk. We used multimodality imaging to identify whether, by midlife, any pregnancy-associated phenotypes were still identifiable and to what extent they could be explained by blood pressure. Participants were identified by review of hospital maternity records 5 to 10 years after pregnancy and invited to a single visit for detailed cardiovascular imaging phenotyping. One hundred seventy-three women (age, 42±5 years, 70 after normotensive and 103 after hypertensive pregnancy) underwent magnetic resonance imaging of the heart and aorta, echocardiography, and vascular assessment, including capillaroscopy. Women with a history of hypertensive pregnancy had a distinct cardiac geometry with higher left ventricular mass index (49.9±7.1 versus 46.0±6.5 g/m2; P=0.001) and ejection fraction (65.6±5.4% versus 63.7±4.3%; P=0.03) but lower global longitudinal strain (−18.31±4.46% versus −19.94±3.59%; P=0.02). Left atrial volume index was also increased (40.4±9.2 versus 37.3±7.3 mL/m2; P=0.03) and E:A reduced (1.34±0.35 versus 1.52±0.45; P=0.003). Aortic compliance (0.240±0.053 versus 0.258±0.063; P=0.046) and functional capillary density (105.4±23.0 versus 115.2±20.9 capillaries/mm2; P=0.01) were reduced. Only differences in functional capillary density, left ventricular mass, and atrial volume indices remained after adjustment for blood pressure (P<0.01, P=0.01, and P=0.04, respectively). Differences in cardiac structure and geometry, as well as microvascular rarefaction, are evident in midlife after a hypertensive pregnancy, independent of blood pressure. To what extent these phenotypic patterns contribute to cardiovascular disease progression or provide additional measures to improve risk stratification requires further study.